Impact of Motivation Enhancing Practices and Mediating Role of Talent Engagement on Turnover Intentions: Evidence from Malaysia - Shah, Syed Haider Ali; Beh, Loo-See (International Review of Management and Marketing, 2016)
Employees are the backbone of any organization. Engaged and motivated employees enable the organization to gain the competitive advantage. Retention of employees is the main concern of organization now a day. The purpose of this study was to examine the direct relationship of motivation enhancing practices on turnover intentions and through talent engagement (Job engagement and Organization engagement) among the managers in hotel industry in Kuala Lumpur. This study investigated engagement in two dimensions. A total of 560 questionnaires were distributed to managers, who were working in three star, four star and five star hotels located in Kuala Lumpur. Structural equation modelling (SEM) was applied to test the hypotheses. The study found that motivation enhancing practices (employee recognition, salary and perks, performance feedback, opportunities for advancement and development job security and workload) have significant negative relationship with employees' turnover intentions. The interesting finding is that job engagement does not mediate between the motivation enhancing and turnover intentions while organization engagement statistically significant mediates the relationship. The findings of this study are important for hotels management to implement these motivation enhancing practices. Management of hotels should pay more attention to these motivation enhancing practices in order to retain the potential managers. Keywords: Motivation enhancing practices, Talent engagement, SEM JEL Classifications: H10, B10